Understory cover increases patch use in rodent Thrichomys fosteri. Issue 3 (4th May 2018) - Menezes, Jorge F.S.; Mourão, Guilherme M.; Kotler, Burt P.
Abstract : Rodent anti-predator behavior has been documented in many different habitats across the world. Most studies found that rodents seek shelter in bushes. However, there is little evidence for this from the tropics, and existing evidence is ambivalent. Thus, we studied rodent anti-predator behavior in a new tropical system: the rodent Thrichomys fosteri in the Pantanal wetlands. We tested two hypotheses: (1) patch use decreases with distance to caraguatá ( Bromelia balansae ) bushes, as it would be expected if they were shelters; (2) canopy cover increases patch use, as it is also a form of cover. To test those hypotheses, we set eight 6 × 4 grids of patches composed of 200 mL of sand and 20.5 g of peanuts. We measured giving-up densities, the leftover food in patch, which is inversely proportional to time in habitat. We found support for hypothesis 1, but also evidence in contradiction of hypothesis 2. We suggest that open areas may be dangerous to the predators of T. fosteri, making these habitats safer than the forests for this rodent. We conclude that this tropical species adheres to global patterns, but only at microhabitat level.